Quercetin attenuates carbon tetrachloride-induced testicular damage in rats - Sönmez, M; Türk, G; Çeribaşı, S; Çiftçi, M; Yüce, A; Güvenç, M; Özer Kaya, Ş; Çay, M; Aksakal, M (My University, 2014)
This study was conducted to investigate the effect of quercetin on carbon tetrachloride (CCl4)-induced sperm damages, testicular apoptosis and oxidative stress in male rats. Group 1 served as control, group 2 was treated with only quercetin, group 3 was treated with only CCl4 and group 4 received CCl4 + quercetin. All administrations were performed by gavage and maintained for 10 weeks. CCl4 administration caused significant decreases in absolute and relative reproductive organ weights, sperm motility, concentration and testicular glutathione peroxidase (GSH-Px) and catalase (CAT) activities, and significant increases in lipid peroxidation (LPO) level, abnormal sperm rate and testicular apoptotic cell index, along with some histopathological damages when compared to the control group. However, administration of CCl4 together with quercetin provided statistically significant improvements in LPO level, abnormal sperm rate, the degree of histopathological lesions and testicular apoptotic cell index when compared to only CCl4 group. In addition, improvements observed in absolute and relative weights of reproductive organs, sperm motility and concentration, and testicular GSH-Px and CAT activities in group 4 were statistically insignificant when compared to only CCl4 group. In conclusion, quercetin has antiperoxidative effect, and its oral administration attenuates the CCl4-induced some damages in male reproductive organs and cells by decreasing the LPO.
Makale - Bilimsel Dergi Makalesi - Çok Yazarlı
Keywords: Apoptosis carbon tetrachloride lipid peroxidation quercetin spermatozoa testis